VD_FINDINFO Jug / 2020 / 327 vom 18. Februar 2020 - VD Tribunal cantonal (2020)
DISPOSITIONS PÉNALES DE LA LSTUP, BRIGANDAGE, TENTATIVEDROIT PÉNAL, LÉSION CORPORELLE GRAVE, LÉSION CORPORELLE SIMPLE, EXPULSIONDROIT PÉNAL | 122 CP, 123 ch. 1 al. 1 CP, 140 ch. 1 CP, 144 al. 1 CP, 66a CP, 19 al. 1 LStup, 19 ch. 2 LStup